The Effect of Organizational Culture and Work Environment on Employee Performance Mediated by Job Satisfaction - Trievanni Chantika; Sulaiman Helmi; Muji Gunarto; Fitriasuri (Indonesian Journal of Business Analytics, 2025)
This study aims to analyze the impact of organizational culture and work environment on employee performance, with job satisfaction as a mediating variable, at PT XX. The research addresses issues such as declining employee performance, high absenteeism, and inequalities in facilities and policies. Using a quantitative approach with causal explanatory design, data were collected from 94 employees through a Google Form-based questionnaire. The results show that organizational culture and work environment significantly influence job satisfaction, which in turn affects employee performance. Organizational culture and work environment positively contribute to performance, with job satisfaction acting as a key factor in improving employee productivity. This study highlights the importance of enhancing organizational culture and work environment to optimize performance.